2020
DOI: 10.1109/access.2020.2980284
|View full text |Cite
|
Sign up to set email alerts
|

Wideband and Bandwidth-Controllable Hybrid-Cylindrical Glass Dielectric Resonator Antenna for Indoor Communication

Abstract: In this paper, a wideband and bandwidth-controllable hybrid-glass dielectric resonator antenna (DRA) excited by a probe platform is proposed. The proposed hybrid-glass DRA simply consists of a probe platform and a solid cylindrical glass DRA unit, making the fabrication easier. The probe mode and the TM 01δ mode of the cylindrical glass DRA are employed to design the wideband antenna. It is found that the impedance bandwidth of this hybrid-DRA can be controlled by the height of the glass DRA in a wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…For indoor communication, omnidirectional antenna has gained in popularity because it is able to provide a relatively wide coverage. In the past three decades, a large number of studies have shown that the dielectric resonator antenna (DRA) [1], [2], [3], [4], [5] owns the merits of low loss, high radiation efficiency and controllable bandwidth. In addition, the electric dipole mode (TM-mode) of the DRA providing the omnidirectional radiation pattern is very easy to be excited [6], [7], [8], [9], making it a good candidate for designing the omnidirectional antenna.…”
Section: Introductionmentioning
confidence: 99%
“…For indoor communication, omnidirectional antenna has gained in popularity because it is able to provide a relatively wide coverage. In the past three decades, a large number of studies have shown that the dielectric resonator antenna (DRA) [1], [2], [3], [4], [5] owns the merits of low loss, high radiation efficiency and controllable bandwidth. In addition, the electric dipole mode (TM-mode) of the DRA providing the omnidirectional radiation pattern is very easy to be excited [6], [7], [8], [9], making it a good candidate for designing the omnidirectional antenna.…”
Section: Introductionmentioning
confidence: 99%